2007
DOI: 10.1016/j.virol.2007.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus-like particle-induced activation of NF-κB and Erk signaling in human dendritic cells requires the glycoprotein mucin domain

Abstract: Dendritic cells (DCs), important early targets of Ebola virus (EBOV) infection in vivo, are activated by Ebola virus-like particles (VLPs). To better understand this phenomenon, we have systematically assessed the response of DCs to VLPs of different compositions. VLPs containing the viral matrix protein (VP40) and the viral glycoprotein (GP), were found to induce a proinflammatory response highly similar to a prototypical DC activator, LPS. This response included the production of several proinflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 59 publications
4
69
0
1
Order By: Relevance
“…In this study, we demonstrated that IFN treatment and/or expression of human ISG15 significantly inhibited release of Ebola VP40-WT VLPs. It is well documented that Ebola virus VP40 can bud indepen- dently as a VLP from mammalian cells (40,46,47,61,65). Efficient release of VP40 VLPs is known to depend on functional L-domain(s) of VP40, and at least two host proteins, tsg101 and Nedd4 (36,48,51,61,62,66).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that IFN treatment and/or expression of human ISG15 significantly inhibited release of Ebola VP40-WT VLPs. It is well documented that Ebola virus VP40 can bud indepen- dently as a VLP from mammalian cells (40,46,47,61,65). Efficient release of VP40 VLPs is known to depend on functional L-domain(s) of VP40, and at least two host proteins, tsg101 and Nedd4 (36,48,51,61,62,66).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of viral antigen in the brains of NiV encephalitis patients postmortem indicates the spread of the virus past the presumed respiratory route of entry (13,27). DCs have also been known to provide privileged havens for viruses and have been indicated in the systemic spread of Ebola virus and Dengue virus (9,21,33,38,44). Additionally, relapse and late-onset encephalitis from Nipah virus infections suggest viral persistence associated with longterm immune evasion (58).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies against Zaire EBOV VP35 and against Zaire EBOV NP were generated in collaboration with the Mount Sinai Hybridoma Center and have been described previously (6,27). A monoclonal antihemagglutinin (anti-HA) antibody was purchased from Sigma (St. Louis, MO).…”
Section: Antibodiesmentioning
confidence: 99%
“…Sequences encoding Zaire EBOV L amino acids 1 to 505 (HA-L amino acids 1 to 505) were amplified from plasmid pTM1-L by PCR (33), cloned with an amino-terminal HA tag, and cloned into pCAGGS. The expression plasmid for Zaire EBOV NP, pcDNA3 EBOV NP, has been described previously (27).…”
Section: Antibodiesmentioning
confidence: 99%